A randomized, controlled, and clinical trial to evaluate the efficacy of electrical vestibular stimulation, compared to a sham control for the management of sleep and autonomic parameters in patients with Parkinson’s disease - Goothy, Sai Sailesh kumar; Gawarikar, Sudhir; Choudhary, Anita; Potey Gajanan Govind; Purohit, Manju; Pathak, Ashish; Chouhan, Rohit Singh; Mahadik Vijay Khanderao (Asian Journal of Medical Sciences, 2022)
Background: Electrical vestibular nerve stimulation (VeNs) was simple, non-invasive, and can administer the stimulus in a controlled manner. The studies related to the application of electrical VeNs in the management of sleep and autonomic parameters were sparse in the Indian population. Aims and Objectives: The present study was undertaken to observe the effectiveness of electrical VeNs in the management of sleep and autonomic parameters in patients with Parkinson’s disease (PD). Materials and Methods: Thirty cases of PD, both the genders, were recruited in the study by convenient sampling after obtaining written informed consent. After recording baseline parameters of Insomnia Severity Index (ISI), systolic and diastolic blood pressure (DBP), and pulse rate, electrical VeNs was administered to the intervention group and placebo stimulation was administered to the control group for 12 weeks. Post-intervention parameters were recorded after 6 weeks and after 12 weeks after the intervention in both control and intervention groups. Results: There was a significant decrease in the ISI scores, pulse rate, and systolic blood pressure after the intervention in the participants of the intervention group. DBP was decreased but was not statistically significant. There was no significant difference in the ISI scores, pulse rate, and systolic and DBP before and after the intervention in the participants of the control group. Conclusion: The present study results support the improvement of sleep followed by electrical VeNs. The study recommends detailed studies in this area to support the incorporation of electrical VeNs in the management strategy of PD.